FRI0207 The incorporation of the antero-posterior lumbar spine view in the modified stoke ankylosing spondylitis spine scoreonly marginally improves detection of radiographic spinal progression in axial spondyloarthritis. (12th June 2018) - Llop, M.; Rios Rodriguez, V.; Sieper, J.; Haibel, H.; Rudwaleit, M.; Poddubnyy, D.
Abstract : Background: The modified Stoke Ankylosing Spondylitis Spine Score (mSASSS) is considered currently as a gold standard of assessment of structural damage in the spine in patients with axial spondyloarthritis (axSpA). However, mSASSS takes into account only structural damage visible on lateral radiographs of the cervical and lumbar spine. Antero-posterior (AP) views might be able to detect structural damage not visible on lateral ones. Objectives: To evaluate the performance of the extended mSASSS score including AP lumbar radiographs compared to the conventional mSASSS in detection of radiographic spinal progression in patients with axSpA. Methods: A total of 210 patients with axSpA, 115 with ankylosing spondylitis and 95 with non-radiographic axSpA, from the GErman SPondyloarthritis Inception Cohort (GESPIC) were included in the analysis based on the availability of spinal radiographs (cervical spine lateral view, lumbar spine lateral and AP views), at baseline and year 2. Two trained readers independently scored lateral cervical and lumbar spine images according to the mSASSS system (0–72). In addition, left and right, upper and lower vertebral corners of vertebral bodies visible on lumbar AP radiographs (lower Th12 to upper S1) were assessed according to the same scoring system ranging from 0 (no abnormality) to 3 (bridging syndesmophyte). Thus, the extended mSASSS had a total range from 0 to 144. The reliability and the sensitivity to detect radiographic spinal progression of the extended mSASSS as compared to the conventional mSASSS were evaluated. Following definitions for progression were used: change of the absolute scores, change of ≥2 points, development of new syndesmophytes, and development of new syndesmophytes or growth of the existing syndesmophytes after 2 years. Results: The reliability of both scores was excellent with intraclass correlation coefficients (ICCs) of 0.927 and 0.926 at baseline and 0.933 and 0.920 at year 2 for the extended and conventional mSASSS, respectively. The mean ±SD score at baseline was 4.25±8.32 and 8.59±17.96 for mSASSS and extended mSASSS, respectively. The change score between baseline and year 2 was 0.73±2.34 and 1.19±3.73 for mSASSS and extended mSASSS, respectively (table 1). With the extended mSASSS score as compared to the conventional one, new syndesmophytes after 2 years were detected in 4 additional patients (1.9%), new syndesmophytes or progression of existing syndesmophytes – in 5 additional patients (2.4%), and progression by ≥2 points in the total score – in 14 additional patients (6.7%) – table 1. Conclusions: The incorporation of the AP radiographs of the lumbar spine in the assessment of structural spinal damage provided only a relatively small improvement of detection of radiographic spinal progression in axSpA. Acknowledgements: GESPIC was financially supported by the German Federal Ministry of Education and Research (BMBF) 2000–2007. 2005–2009 complementary financial support was obtained also from Abbott/Abbvie, Amgen, Centocor, Schering-Plough, and Wyeth. Since 2010 GESPIC is supported by Abbvie. The work of Maria Llop was supported by EULAR Scientific Bursary and by FER Institution (Fundación Española de Reumatología). Disclosure of Interest: M. Llop: None declared, V. Rios Rodriguez Consultant for: Abbvie, Novartis, J. Sieper Grant/research support from: Abbvie, MSD, Pfizer, Consultant for: Abbvie, MSD, Pfizer, UCB, H. Haibel: None declared, M. Rudwaleit Consultant for: Abbvie, MSD, Pfizer, UCB, D. Poddubnyy Grant/research support from: Abbvie, MSD, Novartis, Consultant for: Abbvie, BMS, MSD, Novartis, Pfizer, UCB, Speakers bureau: Abbvie, BMS, Janssen, MSD, Novartis, Pfizer, Roche, UCB